Performance Enhancement of a Building-Integrated Photovoltaic/Thermal System Coupled with an Air Source Heat Pump - Edward Vuong; Alan S. Fung; Rakesh Kumar (Energies)
This study explores the improvement of building integrated photovoltaic–thermal (BIPV/T) systems and their integration with air source heat pumps (ASHPs). The BIPV/T collector needs a method to effectively extract the heat it collects, while ASHP can boost their efficiency utilizing preheated air from the BIPV/T collectors. Combining these two systems presents a valuable opportunity to enhance their performance. This paper discusses technological improvements and integration through a comprehensive modelling analysis. Two versions of the BIPV/T systems were assessed using a modified version of EnergyPlus V8.0, a building energy simulation program. This study involved sensitivity analysis of the internal channel surface and cover emissivity parameters of the opaque BIPV/T (OBIPV/T), transparent BIPV/T (TBIPV/T), and building-integrated solar air heater collectors (BISAHs). Various arrangements of the collectors were also studied. A BIPV/T-BISAH array design was selected based on the analysis, and its integration with a net-zero energy house. The BIPV/T-BISAH coupled ASHP system decreased space heating electricity consumption by 6.5% for a net-zero house. These modest savings are mainly attributed to the passive design of the houses, which reduced heating loads during sunny hours/days.